PHARMACOGNOSTIC INVESTIGATION ON ELAEOCARPUS BLASCOI WEIBEL LEAVES - A. VIJAYAN; C. SEBASTIAN RAJASEKARAN (International Journal of Pharma and Bio Sciences, 2010)
Pharmacognostic investigation of the fresh leaves used for anatomical sections of Elaeocarpus blascoi Weibel was carried out to determine its macro- and microscopical characters. Externally, the leaves possess Leaves simple, alternate, spiral, clustered at twig ends; stipules caducous; canaliculate, sparsely adpressed hairy; elliptic-ovate, apex acute to shortly acuminate with blunt tip, base rounded, margin shallowly serrate, glabrous; midrib at the base. Internally, its shows the presences of anomocytic stomata, multicellular, covering trichomes with an acute apex, prism and clustered crystals of calcium oxalate and fiber elements. The chemo-microscopy revealed the presences of lignin, starch grains and calcium oxalate crystals. Physicochemical evaluation includes ash values, extractive values and moisture content. These findings will be useful towards establishing pharmacognostic standards on identification, purity, quality and classification of the plant, which is gaining relevance in plant drug research.